Hybrid and adaptive control of functional electrical stimulation to correct hemiplegic gait for patients after stroke - Dong, Yiqun; Wang, Kangling; He, Ruxin; Zheng, Kai; Wang, Xiaohong; Huang, Guozhi; Song, Rong (Frontiers in Bioengineering and Biotechnology, 2023)
Gait, as a fundamental human movement, necessitates the coordination of muscles across swing and stance phases. Functional electrical stimulation (FES) of the tibialis anterior (TA) has been widely applied to foot drop correction for patients with post-stroke during the swing phase. Although the gastrocnemius (GAS) during the stance phase is also affected, the FES of the GAS received less attention. To address this limitation, a timing-and intensity-adaptive FES control strategy was developed for both the TA muscle and GAS muscle. Each channel incorporates a speed-adaptive (SA) module to control stimulation timing and an iterative learning control (ILC) module to regulate the stimulation intensity. These modules rely on real-time kinematic or kinetic data during the swing or stance phase, respectively. The orthotic effects of the system were evaluated on eight patients with post-stroke foot drop. Gait kinematics and kinetics were assessed under three conditions: no stimulation (NS), FES to the ankle dorsiflexor TA (SA-ILC DS) and FES to the TA and the ankle plantarflexor GAS (SA-ILC DPS). The ankle plantarflexion angle, the knee flexion angle, and the anterior ground reaction force (AGRF) in the SA-ILC DPS condition were significantly larger than those in the NS and SA-ILC DS conditions (P < 0.05). The maximum dorsiflexion angle during the swing phase in the SA-ILC DPS condition was similar to that in the SA-ILC DS condition, with both being significantly larger than the angle observed in the NS condition (P < 0.05). Furthermore, the angle error and force error relative to the set targets were minimized in the SA-ILC DPS condition.The observed improvements can be ascribed to the appropriate stimulation timing and intensity This is a provisional file, not the final typeset article provided by the SA-ILC DPS strategy. This study demonstrates that the hybrid and adaptive control strategy of FES system offers a significant orthotic effect, and has considerable potential for future clinical application.